Characterization of a highly stable α-galactosidase from thermophilic Rasamsonia emersonii heterologously expressed in a modified Pichia pastoris expression system - Jian-Lu An; Wei-Xin Zhang; Wei-Ping Wu; Guan-Jun Chen; Wei-Feng Liu (Microbial Cell Factories, 2019)
Abstract Background Structurally stable α-galactosidases are of great interest for various biotechnological applications. More thermophilic α-galactosidases with high activity and structural stability have therefore to be mined and characterized. On the other hand, few studies have been performed to prominently enhance the AOX1 promoter activity in the commonly used Pichia pastoris system, in which production of some heterologous proteins are insufficient for further study. Results ReGal2 encoding a thermoactive α-galactosidase was identified from the thermophilic (hemi)cellulolytic fungus Rasamsonia emersonii. Significantly increased production of ReGal2 was achieved when ReGal2 was expressed in an engineered Pastoris pichia expression system with a modified AOX1 promoter and simultaneous fortified expression of Mxr1 that is involved in transcriptionally activating AOX1. Purified ReGal2 exists as an oligomer and has remarkable thermo-activity and thermo-tolerance, exhibiting maximum activity of 935 U/mg towards pNPGal at 80 °C and retaining full activity after incubation at 70 °C for 60 h. ReGal2 is insensitive to treatments by many metal ions and exhibits superior tolerance to protein denaturants. Moreover, ReGal2 efficiently hydrolyzed stachyose and raffinose in soybeans at 70 °C in 3 h and 24 h, respectively. Conclusion A modified P. pichia expression system with significantly enhanced AOX1 promoter activity has been established, in which ReGal2 production is markedly elevated to facilitate downstream purification and characterization. Purified ReGal2 exhibited prominent features in thermostability, catalytic activity, and resistance to protein denaturants. ReGal2 thus holds great potential in relevant biotechnological applications.